339 INTRAVENOUS CANGRELOR VERSUS ORAL TICAGRELOR IN PATIENTS WITH ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION UNDERGOING PRIMARY PERCUTANEOUS CORONARY INTERVENTION: A PROPENSITY SCORE-MATCHED ANALYSIS. (15th December 2022) - Scalia, Lorenzo; Sammartino, Sofia; Greco, Antonio; Mauro, Maria Sara; Calderone, Dario; Agnello, Federica; Legnazzi, Marco; Laudani, Claudio; Capranzano, Piera; Capodanno, Davide; Tamburino, Corrado
Abstract: Background: In patients with ST-segment elevation myocardial infarction (STEMI) undergoing primary percutaneous coronary intervention (PCI), potent oral inhibitors of the adenosine diphosphate (ADP)–activated platelet P2Y12 receptor (i.e., prasugrel, ticagrelor) are recommended in addition to acetylsalicylic acid, given as a loading dose as soon as possible, and followed by a maintenance dose. However, the onset of action of oral P2Y12 inhibitors is relatively slower in STEMI patients. In comparison with oral P2Y12 inhibitors, cangrelor has several pharmacokinetic advantages due to its intravenous route of administration, including platelet inhibition within minutes. There is no randomized study so far comparing cangrelor with ticagrelor. The aim of this study was to investigate the comparative effectiveness of intravenous cangrelor and ticagrelor pre-treatment in STEMI patients undergoing primary PCI. Methods: We looked for patients with STEMI undergoing primary PCI at a single high-volume center who were naïve from oral P2Y12 inhibitors at presentation and who received cangrelor (in-lab) or ticagrelor pretreatment. The primary endpoint of the study was a composite of all-cause death, myocardial infarction (MI), definite or probable stent thrombosis and unplanned repeat revascularization within hospital discharge. Secondary outcomes were represented by individual components of the primary composite endpoint, cardiovascular death, non-cardiovascular death, and major bleeding within 72 hours from PCI. Propensity score matching was used to account for potential confounders. Results: A total of 396 patients with STEMI (October 2019-March 2022) met the eligibility criteria and entered the analysis; of them, 186 (47%) received intravenous cangrelor. The ticagrelor loading dose was administered before invasive coronary angiography in 210 patients (53%). In the unadjusted analysis, no statistically significant difference between cangrelor and ticagrelor was observed with respect to the primary composite outcome (odds ratio [OR], 1.49, 95% CI, 0.79 to 2.82; P=0.22) and all the other secondary outcomes. Consistently, after propensity-score matching of 133 matched pairs of patients receiving cangrelor or ticagrelor, no significant differences emerged with respect to the primary outcome (OR, 1.12, 95% CI, 0.44 to 2.85; P=0.81) and all the other secondary outcomes. Conclusion: In patients with STEMI undergoing primary who were naïve from oral P2Y12 inhibitors at presentation cangrelor and ticagrelor yielded similar results. Thanks to its pharmacologic characteristics, cangrelor could be especially useful in the acute setting.